2014
DOI: 10.3892/ijmm.2014.1993
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal injection of amyloid-β peptide accelerates RPE cell senescence and retinal degeneration

Abstract: Abstract. Drusen are considered a hallmark characteristic of age-related macular degeneration (AMD). In our previous study, we found that amyloid-β (Aβ) peptide, a component of drusen, induced the cells of the retinal pigment epithelium (RPE; RPE cells) to enter senescence; however, its effects in vivo remain unknown. Thus, the present study was carried out to explore the in vivo effects of Aβ peptide on RPE cell senescence and senescence-associated inflammation in C57BL/6 mice. C57BL/6 mice received a subreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Both soluble and oligomerised amyloid assemblies have been detected in drusen and RPE of human donor retinas [31]. Sub-retinal administration of Ab42 in mice produced AMD-like symptoms manifested by decline in ERG amplitudes, RPE and photoreceptor degeneration including extensive vacuolation and BrM degeneration further highlighting its pathological involvement [32]. Collectively, these findings point towards a possible association of Ab with AMD pathogenesis.…”
Section: Age-related Macular Degenerationmentioning
confidence: 67%
“…Both soluble and oligomerised amyloid assemblies have been detected in drusen and RPE of human donor retinas [31]. Sub-retinal administration of Ab42 in mice produced AMD-like symptoms manifested by decline in ERG amplitudes, RPE and photoreceptor degeneration including extensive vacuolation and BrM degeneration further highlighting its pathological involvement [32]. Collectively, these findings point towards a possible association of Ab with AMD pathogenesis.…”
Section: Age-related Macular Degenerationmentioning
confidence: 67%
“…For the selection of the drug supply, most similar experiments adopted intravitreal 10,35,38 or subretinal 15,39,40 injection of Ab instead of intravenous injection. Intravitreal or subretinal injection can stimulate local pathogenesis to AMD more effectively than intravenous injection.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the age-induced immune geneexpression changes identified in the array studies have also been observed in vitro. Treatment of RPE cells with the age-related DAMPs, such as AGEs [103], amyloid-b [112][113][114], or oxidized photoreceptor outer segments [98,99], induces the upregulation of proinflammatory genes, such as CCL2, IL-6, TNF-a, and CFB but also reduces immune-regulatory genes (such as CFH [98]). The SASP is a well-known phenomenon in all senescent cells [48].…”
Section: Parainflammatory Autonomous Responses By Rpe Cellsmentioning
confidence: 99%